Utilization Of Ethanol Extract Of Wungu Leaf (Graptophyllum Pictum (L) Griff) Growing In The Pamah Deli Old Area As An Anti-Inflammatory - Meilani, Debi; Miranda, Novia Anisa; Ardiani, Rani; Rahmi, Sofia; Yaturramadhan, Hasni (Pustaka Media Publishing, 2023)
Wungu leaves (Graptophyllum pictum (L) Griff) are often used as traditional medicine, contain several chemical compounds, including alkaloids, glycosides, steroids, saponins, tannins and flavonoids and chemical compounds, thought to have anti-inflammatory properties. The aim of this study was to utilize the ethanol extract of Wungu leaves that grow in the Pamah Deli Tua area, North Sumatra, as an anti-inflammatory. This study included characterization of simplicia, phytochemical screening and testing of the anti-inflammatory activity of the ethanol extract of Wungu leaves (EEDW). Measurement of rat leg volume induced by 1% λ-carrageenan using a plestimometer, observations were made every 30 minutes for 6 hours. This study used 5 treatment groups, namely group I was given 0.5% CMC suspension, group II was given diclofenac sodium at a dose of 4.5 mg/kg BW, group III was given EEDW at a dose of 100 mg/kg BW, group IV was given EEDW at a dose of 200 mg /kg BW, group V was given EEDW at a dose of 400 mg/kg BW. Inflammation percentage and inflammation inhibition percentage were calculated. Data were analyzed by Duncan to see whether or not there was a difference between the groups. The results showed that there were significant differences between the doses of 100, 200 and 400 mg/kg BW, but between the doses of 400 mg/kh BW and diclofenac sodium there were no significant differences. The percentage of inflammation at a dose of 400 mg/kg BW was 3,366 and the percentage of inflammation inhibition was 86,569%. The higher the dose of EEDW the more effective it is as an anti-inflammatory, and the dose of 400 mg/KgBB in rats is the optimum dose of EEDW as an anti-inflammatory.